Efektivitas Penggunaan Media Flashcard Gambar Pada Pembelajaran Menulis Puisi Siswa Kelas XI SMK Multi Mekanik Masmur - Saputri, Anisyah; Faizah AR, Hasnah; Permatasari, Silvia (Jurnal Ilmiah Global Education, 2025)
The aim of this research is to find out whether the use of flashcards with captions helps class XI students at SMK Multi Mekanik Masmur in writing poetry. Writing poetry requires the ability to choose the right words, use appropriate language style, and organize ideas well. Initial observations show that many students experience difficulties in this regard. Therefore, researchers use flashcards equipped with images to provide ideas and visual stimuli that help students write poetry more easily. The hope is that with this media students can more easily choose words, determine themes, and create better poetry. The method used in this research is an experiment with a pre-test and post-test design. Two groups of students were selected: an experimental group with picture cards and a control group without picture cards. Before being given treatment, both groups carried out an initial test (pretest) to measure their ability to write poetry. The experimental group was then given learning materials to write poetry using illustrated flashcards, while the control group studied normally without additional media. After the learning process was complete, both groups were given another test (post-test) to see whether their ability to write poetry had improved. Research shows that using picture cards really helps students write poetry. Students who use this media will be able to choose words better and express their emotions more easily in poetry. This also makes it easier to decide on an appropriate topic and language style. In other words, this flashcard media has proven to be effective in improving students' poetry writing abilities.